2008
DOI: 10.3354/ame01205
|View full text |Cite
|
Sign up to set email alerts
|

High single-cell metabolic activity in Antarctic sea ice bacteria

Abstract: Antarctic sea ice bacteria have historically been examined by techniques that measure bulk community properties. In recognition of the complexity of microbial community structure and function, methods are now available to assess the physiological status of individual bacterial cells. We employed 3 assays: Nucleic Acid Double Staining (NADS), modified Vital Stain and Probe (mVSP) and 5-cyano-2, 3-ditolyl tetrazolium chloride (CTC) to (1) quantify the cell-specific metabolic status of bacteria present in the bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…the sea ice and within the water column, we also observed cDNA regenerated from pufM-RNA in sea ice bacterial cells, which suggests that the cells are actively synthesizing the bchl-a gene within this extreme ecosystem. Bacteria in sea ice are highly metabolically active (Martin et al, 2008) and perhaps bacterial phototrophy provides a selective advantage in such extreme conditions. Microbial energetics within the sea ice is still poorly understood and the ecological importance of the AAnPs in the sea ice environment needs further verification to provide a better understanding of their functions and their contributions to the sea ice 'microbial loop'.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the sea ice and within the water column, we also observed cDNA regenerated from pufM-RNA in sea ice bacterial cells, which suggests that the cells are actively synthesizing the bchl-a gene within this extreme ecosystem. Bacteria in sea ice are highly metabolically active (Martin et al, 2008) and perhaps bacterial phototrophy provides a selective advantage in such extreme conditions. Microbial energetics within the sea ice is still poorly understood and the ecological importance of the AAnPs in the sea ice environment needs further verification to provide a better understanding of their functions and their contributions to the sea ice 'microbial loop'.…”
Section: Resultsmentioning
confidence: 99%
“…The highest numbers of cells, both algal and bacterial, are therefore often found at the bottom 10 cm of the ice (McMinn et al ., 1999; 2010; Lizotte, 2003; Ryan et al ., 2011). The microbial communities in sea ice exhibit significantly higher single‐cell metabolic activity than those in many other marine ecosystems despite the extreme environment (Junge et al ., 2004; Martin et al ., 2008; 2009), and they are highly diverse (Brown and Bowman, 2001; Brinkmeyer et al ., 2003; Murray and Grzymski, 2007; Bowman et al ., 2011). Very recently, the presence ofArchaea has been reported in both the Arctic (Collins et al ., 2010) and Antarctic sea ice (Cowie et al ., 2011), and the newly described copiotrophic Coraliomargarita was found in sufficient abundance to suggest a niche occupation in sea ice (Bowman et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This initial observation indicated an active heterotrophic community, and the subsequent microautoradiographic uptake of radiolabeled compounds such as 14 C-L-serine, 3 H-serine, 3 H-glucose and 3 H-thymidine confirmed community-level activity in the form of DNA synthesis [ 24 , 25 ]. More recent single-cell analyses, including the use of tetrazolium chloride (CTC) and fluorescence in situ hybridization (FISH), have shown that ~80% of the bacteria present in the bottom of Antarctic sea ice have a probe-positive cellular rRNA content and >30% of the cells have an electron transport system that is capable of reducing CTC [ 26 , 27 ]. Most of these cells appear to be heterotrophic bacteria, which either live freely or attached to microalgae or detritus [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…A similar level of activity has previously been reported from this region of the sea ice (Martin et al . 2008), but as in other studies it is not clear whether this response is a direct result of increasing the availability of DOM by melting the ice (Giesenhagen et al . 1999, Martin et al .…”
Section: Discussionmentioning
confidence: 83%
“…However, the high degree of in situ metabolic activity (Martin et al . 2008, 2009) and seasonal coupling between the relative abundance of bacteria and microalgae has led to the identification of an active microbial loop, similar to that of temperate oceanic systems (Sullivan & Palmisano 1984, Azam et al . 1991).…”
Section: Introductionmentioning
confidence: 99%